Layer Partition-based Matching Algorithm of DDM based on Dimension - Thein, Nwe Nwe Myint; Tun, Nay Min (Compusoft: an international journal of advanced computer technology, 2014)
High Level Architecture (HLA) is architecture for reuse and interoperation of simulations. In HLA paradigm, the Runtime Infrastructure (RTI) provides a set of services. Data Distribution Management (DDM) service reduces message traffic over the network. DDM aims to control and limit the data exchanged between federates during federation. Each federate may inform the RTI about its intention to publish some data or it may subscribe to receive a subset of the published data. DDM services are used to reduce the transmission and receiving of irrelevant data and aimed at reducing the communication over the network. This paper compares the performance of the layer partition-based matching algorithm based on the result of previous calculated dimension. The algorithm chooses the dynamic pivot based on regions distribution in the routing space. The proposed algorithm firstly calculates the regions distribution. Then, the partitioning among regions performs based on the result of choosing pivot based on region detection and defines the matching area that entirely covers all regions which need to match with regions at pivot point.